Co-creating social innovation in quadruple helixes: evidence from Sweden - Öberg, Åsa; Albats, Ekaterina; Stefan, Ioana; Johansson, Peter E. (Proceedings of ISPIM Conferences, 2021)
In an increasingly globalized world, the challenges of society need to be tackled not by single organisations but by a multitude of stakeholders. Universities can contribute by extending their role and by collaborating with external stakeholders. This study employs qualitative methods to explore how a university engages with its innovation ecosystem through two different projects.The findings, connected to the development of educational and digital systems,show: 1) evidence of two extreme approaches to external stakeholder engagement and 2) three levels of tensions (multi-layered tensions) - on an overarching level, between stakeholder groups, and within groups of stakeholders. The contribution connects to literature on open innovation, quadruple helixes and lastly to university social innovation, especially responsibility diffusion.
N'AVONS PAS ACCÈS
Keywords: Co-création; Europe; Quadruple helix approach